Role of plasmids in antibiotic resistance in clinical infections and implications for epidemiological surveillance: a review - Ayodele Oluwaseun Ajayi; Olajide Joseph Akinjogunla; Adebowale Toba Odeyemi; Akinyomade Oladipo Owolabi (All Life)
The global upsurge in antibiotic resistant bacteria (ARB) is putting immense pressure on healthcare. The spreading of antimicrobial resistance is facilitated by mobile genetic elements, most especially plasmids. The widespread use of antibiotics in clinical and veterinary environments creates selective pressure that drives the evolution of ARB. Plasmids contribute to the propagation of AR in different types of clinical infections. The role plasmids play in this evolution necessitates their utilization in molecular surveillance to detect the emergence of ARB and track the spread of AR plasmids. Recent technologies like replicon typing and whole genome sequencing (WGS) have become the gold standard for molecular epidemiology of plasmids for the detection and control of epidemics in clinical settings. Unfortunately, access to such technologies is limited in low- and middle-income countries (LMICs). The major aim of this review is to examine the specific contributions of plasmids to the upsurge of AR in clinical settings and elucidate the various replicon types that have been attributed to specific antibiotic-resistant infections in healthcare settings. Healthcare in LMICs should be supported to build capacity in WGS and molecular surveillance to effectively prevent and control AR bacterial infections.